2021
DOI: 10.3390/ijerph18073426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Life and Satisfaction in Patients with Fixed Prostheses on Zygomatic Implants Compared with the All-on-Four Concept: A Prospective Randomized Clinical Study

Abstract: Purpose: No published research has compared patients’ quality of life and satisfaction with fixed prostheses supported by zygomatic implants with those supported by all-on-four prostheses. The aim of this study was to evaluate patients’ quality of life and satisfaction with fixed prostheses on zygomatic implants compared with the all-on-four concept. Materials and Methods: A total of 80 patients with atrophic edentulous maxillae were randomized into two groups: Group 1 (rehabilitated with fixed prostheses supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The four final studies selected were randomised controlled trials published in English (Fernández Olarte et al 2015;Felice et al, 2020;Pistilli et al, 2020;Fernández-Ruiz et al, 2021). One study was a split mouth randomised controlled trial and the remaining were 2-arm parallel design randomised controlled trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four final studies selected were randomised controlled trials published in English (Fernández Olarte et al 2015;Felice et al, 2020;Pistilli et al, 2020;Fernández-Ruiz et al, 2021). One study was a split mouth randomised controlled trial and the remaining were 2-arm parallel design randomised controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias of the included studies are represented in Figure 6. conducted by Fernández Olarte et (2015) and Fernández-Ruiz et al (2021). They had a high risk of bias due to no explanation regarding the blinding process.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…Another common option and alternative for the rehabilitation of the atrophic maxilla are zygomatic fixtures. Several studies indicated a high success rate and predictability [ 18 , 19 , 20 , 21 ]. However, there are no clinically applicable criteria for success and the definition of “success” is used as a very flexible term.…”
Section: Discussionmentioning
confidence: 99%
“…An exception is the study by Fernández-Ruiz et al (2021). These authors examined the quality of life and satisfaction in 40 patients who were rehabilitated with fixed prostheses supported by a combination of zygoma fixtures and conventional implants (anterior region) [ 19 ]. Patients’ follow-up treatments were 19.40 ± 4.37 months and a mean VAS of 18.48 ± 3.42 was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The OHIP-EDENT is a commonly utilized tool, considered principally described and demonstrated good reliability and validity. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%